2011
DOI: 10.1177/1545109711401409
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Post-Exposure Prophylaxis (PEP) against HIV Infection among Health Care Providers in a Tertiary Hospital in Nigeria

Abstract: The study shows that the knowledge and practice of PEP among health care providers are very poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 9 publications
(12 reference statements)
13
44
9
Order By: Relevance
“…This finding is lower compared to other study which was conducted in a tertiary hospital in Nigeria (97%) and Gonder in Ethiopia (92.8%) [15,16], respectively. Considerably high proportions (63 %) of nursing and midwifery students were knowledgeable about PEP of HIV in this study area.…”
Section: Characteristics Number (%) Total (%)contrasting
confidence: 74%
See 1 more Smart Citation
“…This finding is lower compared to other study which was conducted in a tertiary hospital in Nigeria (97%) and Gonder in Ethiopia (92.8%) [15,16], respectively. Considerably high proportions (63 %) of nursing and midwifery students were knowledgeable about PEP of HIV in this study area.…”
Section: Characteristics Number (%) Total (%)contrasting
confidence: 74%
“…So when they are students they need to have an adequate knowledge and a positive attitude towards healthcare problems including HIV/ AIDS which has recently become a major public health concern in the country [15,16]. In contrary to their roles, studies from different countries have reported a poor knowledge among the nurses regarding HIV/AIDS [17].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…It is similar to the exposures in Ethiopia (33.8%) 4 and Nigeria (33%), but much lower as compared to studies carried out in Jimma (68.5%). 5,6 In Ethiopia, 74.2% of the exposed population took PEP regimen with 46.9% taking it within 2 hrs of exposure and 79.6% completing the treatment; while in Nigeria, 23.1% took PEP regimen and all of them completing the course. 4,5 In the study conducted in Gujarat, it was observed that 56.8% initiated treatment within 2 hrs and 94% completed the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In Ethiopia, 74.2% of the exposed population took PEP regimen with 46.9% taking it within 2 hrs of exposure and 79.6% completing the treatment; while in Nigeria, 23.1% took PEP regimen and all of them completing the course. 4,5 In the study conducted in Gujarat, it was observed that 56.8% initiated treatment within 2 hrs and 94% completed the treatment. 7 Only sixteen people who warranted treatment have taken PEP on exposure to HIV risks in our study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Whilst most studies on the efficacy of PEP are derived from animal models, retrospective data from prevention of mother-to-child transmission (PMTCT) studies and occupational exposure support the efficacy in human subjects and also among health care providers in Europe and the U.S. 1,5,6 Health care providers are at risk of occupational HIV acquisition worldwide with 3/1000 injuries resulting in HIV transmission after percutaneous exposure from an HIV infected patient in health settings. [7][8][9] Several studies have explored knowledge on PEP for HIV among healthcare providers as a whole, nurses, medical doctors, surgical residents, midwifery students, medical interns and dental students.…”
Section: Introductionmentioning
confidence: 99%